2020
DOI: 10.1080/13880209.2020.1797124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Jiedu Huoxue decoction on rat model of experimental nonbacterial prostatitis via regulation of miRNAs

Abstract: Context: The underlying mechanisms of Jiedu Huoxue decoction (JDHXD) in treating chronic prostatitis have not been fully explored. Objective: This study investigates the miRNAs as potential biomarkers and the effect of JDHXD on the rat model of experimental nonbacterial prostatitis. Materials and methods: Fifty-four Sprague-Dawley male rats were randomly divided into normal control, model, JDHXD low dose (0.5 g/kg/day), medium dose (1 g/kg/day), high dose (2 g/kg/day) and western medicine (cernilton 0.094 g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The YQJPR group continued the TCM intervention after the 12th week of modelling, and the whole TCM intervention lasted for 12 weeks. The dose of YQJPR to rats was calculated from the dose conversion method between humans and rats [ 15 ]. The adult clinical dosage of YQJPR was 1.786 g/(kg·d), and then, the YQJPR group was given 11.25 g/(kg·d) by gavage, while the control and model groups were given the same amount of normal saline by gavage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The YQJPR group continued the TCM intervention after the 12th week of modelling, and the whole TCM intervention lasted for 12 weeks. The dose of YQJPR to rats was calculated from the dose conversion method between humans and rats [ 15 ]. The adult clinical dosage of YQJPR was 1.786 g/(kg·d), and then, the YQJPR group was given 11.25 g/(kg·d) by gavage, while the control and model groups were given the same amount of normal saline by gavage.…”
Section: Methodsmentioning
confidence: 99%
“…e YQJPR group continued the TCM intervention after the 12th week of modelling, and the whole TCM intervention lasted for 12 weeks. e dose of YQJPR to rats was calculated from the dose conversion method between humans and rats [15].…”
Section: 82mentioning
confidence: 99%
“…The adult dose of HZJDD was 192 g/d. By calculating the dose conversion coefficient per kilogram of body weight between animals and humans (Phok et al, 2017;Du et al, 2021), when the adult standard body weight is 60 kg, the equivalent dose of HZJDD in rats was about 20 g/kg/d, so the doses in this study were 10, 20, and 40 g/kg/d respectively (Yan et al, 2020).…”
Section: Experimentals Animals and Modelingmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a class of small RNA molecules of 17–25 bp in length, play a crucial role in the mediation of gene expression. 5 As non-traumatic biomarkers, miRNAs have been reported to be stably expressed in the blood and dysregulated in various diseases. 6 With advancing research, more miRNAs have been found to be aberrantly expressed in metabolic and cardiovascular diseases: 7 For example, miR-33 and miR-34a appear to be involved in the metabolism of fat, sugar, and cholesterol in the liver.…”
Section: Introductionmentioning
confidence: 99%